Implementasi Model Pembelajaran Berdiferensiasi dalam Meningkatkan Kompetensi Bahasa Inggris Maritim Mahasiswa Perguruan Tinggi Pelayaran di Indonesia - Endah Fauziningrum; Encis Indah Suryani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to examine the implementation of a differentiated learning model in improving maritime English language competency among maritime college students in Indonesia. The background of this study is based on the maritime world's need for graduates with good English language competency, especially in professional and technical contexts. The approach used was a mixed method, namely a combination of quantitative and qualitative methods within a classroom action research framework implemented over two learning cycles. Data were collected through English language competency tests, observations, and in-depth interviews. The results showed a significant increase in all aspects of maritime English competency. The highest increase occurred in speaking skills at 44.38%, while the lowest increase was in maritime vocabulary comprehension at 30.25%. After the implementation of the differentiated learning model, 78.33% of students were in the